2023
DOI: 10.1021/acs.inorgchem.2c03509
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Behavior of Hydrogen Bonded Water in Oligomerization of Silicates

Abstract: Even though much research has been done to demonstrate the oligomerization of zeolites and silicates, there has been almost no study that investigates the role of hydrogen bonds in these reaction pathways. This study demonstrates the catalytic activity of hydrogen bonds in the silicate oligomerization reaction pathway. The presence of hydrogen bonding has been shown to enhance the energetic favorability of the anionic-I mechanism. Catalysis is prevalent in the Si–OH rupture process of the reaction pathway. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Today, water content is acknowledged as a critical synthesis variable in zeolite synthesis. It has been shown to impact both gelation and crystallization kinetics, and to influence the final aluminum content as well as the framework topology . With increasing water content, phase transitions from Na-SOD to Na-LTA, , K-EDI to K-CHA, and Na-MOR to Na-MFI, have been reported, with certain topologies requiring more dilute synthesis systems.…”
Section: Introductionmentioning
confidence: 99%
“…Today, water content is acknowledged as a critical synthesis variable in zeolite synthesis. It has been shown to impact both gelation and crystallization kinetics, and to influence the final aluminum content as well as the framework topology . With increasing water content, phase transitions from Na-SOD to Na-LTA, , K-EDI to K-CHA, and Na-MOR to Na-MFI, have been reported, with certain topologies requiring more dilute synthesis systems.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with CASC, it is observed that the bond lengths between Ag and Cl atoms and Sb and Cl atoms were determined to be 2.755 Å and 2.624 Å, respectively. The lengths of the apical bonds ( d abl ) and the equatorial bonds ( d ebl ) are respectively given by 77 where a and c are the lattice parameters and u are the positional parameters of the Cl atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The Sn 1– x Fe x O 2 octahedron was distorted, with the apical Sn or Fe–O bond length marginally longer than the equatorial Sn or Fe–O bond length. The lengths of the apical bonds ( d abl ) and the equatorial bonds ( d ebl ) are, respectively, given by d normala normalb normall = a u 2 d normale normalb normall = 0.5 a .25em false[ 2 false( 2 u 1 false) 2 + false( c / a false) 2 false] 1 / 2 where a and c are the lattice parameters and u is the positional parameter of the O atoms. The Sn or Fe atoms possess Wyckoff sites (0, 0, 0), (1/2, 1/2,1/2).…”
Section: Resultsmentioning
confidence: 99%
“…The Sn 1−x Fe x O 2 octahedron was distorted, with the apical Sn or Fe−O bond length marginally longer than the equatorial Sn or Fe−O bond length. The lengths of the apical bonds (d abl ) and the equatorial bonds (d ebl ) are, respectively, given by80…”
mentioning
confidence: 99%